Production of leaf wax n-alkanes across a tropical forest elevation transect - Feakins, S; Peters, T; Wu, M; Shenkin, A; Salinas, N; Girardin, C; Bentley, L; Blonder, B; Enquist, B; Martin, R; Asner, G; Malhi, Y (Elsevier, 2016)
Waxy compounds form the boundary layer of the living leaf and contribute biomarkers to soils, and lake and marine sediments. Cataloging the variation in leaf wax traits between species and across environmental gradients may contribute to the understanding of plant functional processes in modern ecosystems, as well as to calibration efforts supporting reconstruction of past ecosystems and environments from the sedimentary archives of leaf wax biomarkers. Towards these goals, we have surveyed the distributions of leaf wax n-alkanes in trees from the lowland tropical rainforest (TR) and montane cloud forest (TMCF) of Perú. Molecular abundances were quantified via gas chromatography flame ionization detection (GC-FID) for 632 individuals, 152 species, 99 genera and 51 families across 9 forest plots spanning 0.2–3.6 km elevation. We found the expected abundance distributions; for example, they were dominated by long chain, odd numbered n-alkanes, especially C29 and C31. New observations included a tendency to increasing total alkane concentration at higher elevation. We propose that the well known leaf economic strategy to increase leaf mass per unit area with elevation, provides a theoretical basis for understanding the increase in leaf wax n-alkane abundance with elevation: we infer an increased investment in foliar defense associated with increased leaf lifespan and in response to environmental pressures including cloud immersion and declining temperature. Furthermore, we combined measurements of n-alkane concentration with estimates of forest productivity to provide new ways to quantify ecosystem-scale forest alkane productivity. We introduce a new concept of n-alkane net primary productivity (NPPalk; the product of alkane concentration and leaf NPP) and find that alkane productivity estimates range from 300 to 5000 g C/ha/yr, associated with ecological and environmental changes across the elevation profile.